Implementasi Prinsip Keadilan dalam Kebijakan Otonomi Khusus Papua Tinjauan Fiqih Siyasah Dusturiyah - Afifah Afrah Mumtazah; Sajida Alvi Batubara; Na'ilah Siti Nabila; Azrul Aldy Pratama; Munawar Al Ansor (Albayan Journal of Islam and Muslim Societies, 2025)
The Special Autonomy Policy for Papua was established as a constitutional instrument to address development disparities, socio-political conflicts, and the marginalization of indigenous Papuans within the national governance system. This study aims to analyze the implementation of the principle of justice in the Special Autonomy Policy for Papua through the perspective of fiqh siyasah dusturiyah. This study employs a qualitative approach using a literature review method. Data were obtained from various academic journals discussing special autonomy, social justice, indigenous peoples’ rights, decentralization, development in Papua, and the concept of justice in Islamic law. The research findings indicate that the implementation of the Papua Special Autonomy Policy has not fully reflected the principles of substantive justice as developed in fiqh siyasah dusturiyah. Development disparities, weak participation of indigenous communities, budget distribution issues, and low oversight effectiveness are the main factors hindering the realization of social justice in Papua. From the perspective of constitutional political jurisprudence, the government bears a moral and constitutional responsibility to ensure the public welfare through policies that are fair, transparent, and oriented toward the people’s well-being. The principle of justice in Islam emphasizes a balance of rights and obligations, protection of vulnerable groups, and equitable development without discrimination. Therefore, the implementation of Papua’s Special Autonomy requires strengthening of governance, budget oversight, empowerment of indigenous communities, and the reconstruction of policies to be more participatory so that the goal of social justice can be optimally achieved.